Essentials of understanding psychology - Feldman, Robert S. (McGraw Hill, 2011)
Its new groundbreaking adaptive diagnostic tool generates a personalised study plan to help students “know what they know” while guiding them to understand and learn what they don't know through engaging interactivities, exercises, and readings. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective.